2012
DOI: 10.1080/10550887.2011.642766
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Social Development in Preschool Children Born to Women Using Substances

Abstract: Prenatal substance exposure is associated with physical birth defects and increased risk of regulatory and neuropsychological difficulties of children born to mothers using substances while pregnant. Myriad factors, such as maternal psychopathology, stress, and poor living circumstances, may influence childhood development in addition to the teratological effect of prenatal substance exposure. This study explores the long-term developmental consequences in children from birth to age 7 born to women using subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…Only 3 studies reported FM outcomes for children with "no/low" PAE ,0.14 oz per day (,2 drinks per week), 34 low PAE (1-4 drinks per week), 31 or light/moderate PAE (0-1 oz per day or 0-14 drinks per week). 30,33,35 Thirteen studies only in-cluded children with moderate or high PAE or children with pFAS or FAS (who likely had "moderate to high" PAE as these diagnoses include the most severe effects of PAE). 30,33,35 Thirteen studies only in-cluded children with moderate or high PAE or children with pFAS or FAS (who likely had "moderate to high" PAE as these diagnoses include the most severe effects of PAE).…”
Section: Fetal Alcohol Spectrum Disorders and Prenatal Alcohol Exposurementioning
confidence: 99%
“…Only 3 studies reported FM outcomes for children with "no/low" PAE ,0.14 oz per day (,2 drinks per week), 34 low PAE (1-4 drinks per week), 31 or light/moderate PAE (0-1 oz per day or 0-14 drinks per week). 30,33,35 Thirteen studies only in-cluded children with moderate or high PAE or children with pFAS or FAS (who likely had "moderate to high" PAE as these diagnoses include the most severe effects of PAE). 30,33,35 Thirteen studies only in-cluded children with moderate or high PAE or children with pFAS or FAS (who likely had "moderate to high" PAE as these diagnoses include the most severe effects of PAE).…”
Section: Fetal Alcohol Spectrum Disorders and Prenatal Alcohol Exposurementioning
confidence: 99%
“…These children often perform poorly on working memory and IQ tests (Mattson, Goodman, Caine, Delis, & Riley, 1999; Mattson, Riley, Gramling, Delis, & Jones, 1997; Rasmussen, Soleimani, & Pei, 2011) and are more likely to require special education services. These disabilities often extend beyond scholastic performance and can affect social interactions, executive functioning, impulse control, and emotion regulation, often resulting in higher rates of incarceration and mental illness in adulthood (Franklin, Deitz, Jirikowic, & Astley, 2008; Irner, Teasdale, & Olofsson, 2012; Kodituwakku, Handmaker, Cutler, Weathersby, & Handmaker, 1995; Pei, Job, Kully-Martens, & Rasmussen, 2011; Stevens et al, 2012; Streissguth et al, 2004). …”
Section: Alcohol As a Teratogenic Agentmentioning
confidence: 99%
“…As adults, individuals with FASDs are more likely to have trouble with the law, in part due to executive functioning and impulse control deficits (Franklin et al, 2008; Irner et al, 2012; Kodituwakku et al, 1995; Pei et al, 2011; Stevens et al, 2012; Streissguth et al, 2004). To some degree, the learning and memory dysfunctions observed in humans with FASDs (Uecker & Nadel, 1996) have been modeled in animals as well.…”
Section: Interactions Between Developmental Alcohol Exposure and Nmentioning
confidence: 99%
“…In humans, children with FASD have impaired hand-eye coordination [33] and smaller cerebellar vermes compared to age-matched control children [30,31]. Additionally, in clinical studies of cases of children who died with a diagnosis of FAS, cerebellar abnormalities were reported, possibly due in part to hydrocephaly [34,35].…”
Section: Fetal Alcohol Spectrum Disorders Adolescent Drinking Andmentioning
confidence: 99%
“…When presented with a social dilemma and asked to generate solutions to the problem, children with FASD came up with fewer relevant solutions compared to age-matched controls. In addition, Irner and colleagues [33] found that preschool children who were exposed to alcohol in utero had lower scores on a personality and social skill subscale of the Griffiths Mental Development Scales, regardless of environmental factors such as the mother’s social background. Overall, these data suggest that prenatal alcohol exposure can have long-lasting detrimental effects on social intelligence and interpersonal skills.…”
Section: Fetal Alcohol Spectrum Disorders Adolescent Drinking Andmentioning
confidence: 99%